Genetic insights into spike trait inheritance in wheat for drought resilience (Zoo Botanica, 2025)
This study genetic insights of spike-related inheritance traits in wheat (Triticum aestivum L.) under water stress. Seven wheat genotypes, comprising five drought-tolerant and two drought-sensitive lines, were crossed in all possible combinations in complete diallel fashion. The F1 hybrids and parental lines were tested under both irrigated and drought conditions in a randomized complete block design. Traits such as spikes plant-1, spike length, spikelets spike-1, spike weight, grains spike-1, spike harvest index, and grain yield plant-1 were recorded and analyzed.Significant genotypic variation was observed across all traits, with additive gene and partial dominance identified as the primary genetic mechanisms. Heritability estimates were moderate to high (40%–78%), highlighting the potential for genetic improvement. Traits like spikes per plant and spike length displayed high heritability under drought conditions, making them suitable targets for early-generation selection. The findings suggest that breeding programs focusing on additive gene action can enhance drought tolerance and yield potential in wheat. This research provides a framework for developing high-yielding, resilient wheat varieties suited for water-limited environments, through Identification of drought resilient crosses on the basis of studied traits contributing to sustainable food production also.
Keywords: Triticum aestivum; screening; genetic analysis; spike traits; moisture stress